Review Of Islamic Law On The Practice Of Buying And Buying Used Clothing - Intan Merdekawati (ASIAN PUBLISHER, 2023)
This research aims to describe the review of islamic law on the practice of buying and buying used clothing. this type of research is qualitative research and normative legal research; which we know as library legal research. the data sources used by the author in this article include primary legal materials, namely applicable laws and regulations which provide an overview of primary legal materials in the form of interpretations, general books, journals, documents and other references related to this article. the results of writing this article are: first, buying and selling used clothes can be done if the clothes do not cause negative effects (harm) on the buyer's body. second, buying and selling used clothes can be done if the terms and conditions of the sale and purchase must be met. third, there is the right of khiyar (to choose), in this case if the seller experiences a defect during the sale and purchase or afterwards, before delivery occurs, he has the right to khiyar, but if in the transaction both parties know and are mutually willing, then there is no need for khiyar.